DESAIN GAME PELUANGKU BERBASIS CONSTRUCT 2 UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA DAN LITERASI DIGITAL SISWA - Abyater Kustiyarto, Rufus; Hetty Marhaeni, Nafida; Darmawan Arrosyid, Endi; Rafi Fajar Rizky, Muhammad (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
This study aims to develop an educational game-based learning media called "PeluangKu," utilizing Construct 2 to enhance students' understanding of mathematical concepts and digital literacy, particularly in probability topics. The research applied the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) with participants from eighth-grade students at SMP Negeri 7 Yogyakarta. The game incorporates interactive features such as probability materials, level-based challenges, and automated evaluations, integrated with engaging visuals and narratives to boost students' learning motivation. The findings indicate that "PeluangKu" effectively improves students' comprehension of probability concepts, with a feasibility score of 3.8 out of 5. This media also strengthens students' digital literacy by integrating technology into the learning process. The study concludes that the "PeluangKu" educational game is an innovative alternative learning media that can be applied to support interactive mathematics education.